FocVel1 influences asexual production, filamentous growth, biofilm formation, and virulence in Fusarium oxysporum f. sp. cucumerinum - Li, Peiqian; Pu, Xiaoming; Feng, Baozhen; Yang, Qiyun; Shen, Huifang; Zhang, Jingxin; Lin, Birun (Frontiers in Plant Science, 2015)
Velvet genes play critical roles in the regulation of diverse cellular processes. In current study, we identified the gene FocVel1, a homolog of Fusarium graminearum VelA, in the plant pathogenic fungus F. oxysporum f. sp. cucumerinum. This pathogen causes the destructive disease called cucumber Fusarium wilt, which severely affects the production and marketing of this vegetable worldwide. Transcript analyses revealed high expression of FocVel1 during conidiophore development. Disruption of the FocVel1 gene led to several phenotypic defects, including reduction in aerial hyphal formation and conidial production. The deletion mutant ⊿FocVel1 showed increased resistance to both osmotic stress and cell wall-damaging agents, but increased sensitivity to iprodione and prochloraz fungicides, which may be related to changes in cell wall components. In the process of biofilm formation in vitro, the mutant strain ⊿FocVel1 displayed not only a reduction in spore aggregation but also a delay in conidial germination on the polystyrene surface, which may result in defects in biofilm formation. Moreover, pathogenicity assays showed that the mutant ⊿FocVel1 exhibited impaired virulence in cucumber seedlings. And the genetic complementation of the mutant with the wild-type FocVel1 gene restored all the defects of the ⊿FocVel1. Taken together, the results of this study indicated that FocVel1 played a critical role in the regulation of various cellular processes and pathogenicity in F. oxysporum f. sp. cucumerinum.